2023
DOI: 10.1002/cbdv.202201103
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Biological Activity Evaluation and Action Mechanism of Myricetin Derivatives Containing Thiazolebisamide

Abstract: The plant diseases caused by a variety of pathogens such as viruses, bacteria and fungi pose a great threat to global food production and food safety. Therefore, the search for green, efficient and pollution-free pesticides has become an important task. In this article, 23 myricetin derivatives containing thiazolebisamides active groups have been designed and synthesized. Their activities were evaluated by performing in vitro antibacterial and in vivo antiviral assays, microscale thermophoresis (MST) and molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In this study, indole and thiosemicarbazide were used as substrates, and intermediates 1 – 3 and target compounds Z1-Z24 were synthesized by previously reported methods. Supporting Information contained detailed steps for the preparation of intermediates 1 – 3 and target compounds Z1-Z24 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, indole and thiosemicarbazide were used as substrates, and intermediates 1 – 3 and target compounds Z1-Z24 were synthesized by previously reported methods. Supporting Information contained detailed steps for the preparation of intermediates 1 – 3 and target compounds Z1-Z24 .…”
Section: Methodsmentioning
confidence: 99%
“…The effect of the most active Z2 on B.c . was observed on an optical microscope, following the methodology published previously . Experimental results were included in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It possesses a variety of biological activities such as antimicrobial, antioxidant, antimutagenic, anticarcinogenic, anti-inflammatory, antiallergic, analgesic activities and so on, 18,19 and thus has attracted a great deal of attention from researchers. In the previous studies of our group, the derivatives of myricetin were found to possess a variety of biological activities such as anticancer, 20 antiviral, [21][22][23] antibacterial, [24][25][26] and antifungal activities, 27,28 which provides a new idea for the discovery of new green pesticides.…”
Section: Introductionmentioning
confidence: 99%